The Little Green Data Book 2007 - World Bank (Washington, DC, 2012)
The 2007 edition of the little green data book includes a new focus section, four introductory pages that focus on a specific issue related to development and the environment in this edition, carbon dioxide emissions. The reports deem human causation of climate change to be very likely. Late 2006 saw the publication of the Stern review on the economics of climate change, which emphasizes the major economic costs of climate change under different emission scenarios and suggests that early action to curb emissions will reduce costs substantially. As a response to this renewed attention to climate change, the focus section of the little green data book 2007 takes a closer look at carbon dioxide emissions.